Variation in seed mineral elements profile and yield in field bean (Vicia faba L. var. minor) genotypes - Lombardo, Sara; Pandino, Gaetano; Pesce, Gaetano Roberto; Anastasi, Umberto; Tuttobene, Rosalena; Mauromicale, Giovanni (Italian Journal of Agronomy, 2016)
Field bean (Vicia faba L. var. minor) is one of the major leguminous crops cultivated in the world and mainly destined for animal feed. Although its seed is generally recognised as a good protein source, little is known about its mineral elements profile, which is an important aspect for a balanced animal diet. Therefore, the aim of the present work was to assess the seed mineral elements composition, along with some key production parameters, in eight field bean genotypes grown in a Mediterranean environment, without intensive management, over two years (2009/10 and 2010/11). Independently of the year, the seed of Chiaro di Torre Lama was the richest in phosphorus (P), magnesium, calcium and iron contents, while that of Sint 6 and Motta Chiaro 69 were the most effective accumulators of potassium and zinc, respectively. While all the genotypes yielded better in the second year (with more rainfall), the seasonal effect on seed mineral elements composition depended on the genotype. Indeed, the P content was 46% lower in Chiaro di Torre Lama, Motta Chiaro 69 and Sint 6 in the second year, while there was only a negligible seasonal effect for Sint 8 with respect to Fe content. Overall, this crop is reasonably productive under a low management regime and its seed can supply significant amounts of certain minerals (particularly P) in feed formulations. Both aspects are important in a perspective of optimising field bean production in the Mediterranean area and, hence, improving farmers’ income.